ANALISIS STABILITAS LERENG DENGAN METODE ELEMEN HINGGA (STUDI : PROYEK NEW PRIOK CONTAINER TERMINAL) - Anggraini, Nita (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2023)
eographically, Indonesia is a maritime country that has around seventeen thousand islands stretchingfrom Sabang to Merauke so that Indonesia has been named the largest archipelagic country in the world.From the economic sector, Indonesia is also a country with a fairly stable level of economic growth. Thisbackground shows that there are a lot of economic activities in Indonesia. Economic activity in Indonesianwaters is supported by carrying out many maritime infrastructure developments, one of which is theconstruction of a container terminal at Tanjung Priok port. During the construction phase, there is adredging process around Jakarta Bay and it is feared that it will disrupt the stability of the sand bund dueto the dredging process. This study provides an illustration of how the distance between the sand bund anddredging and the slope of the slope greatly affect the safety factor. Slope stability analysis study using finiteelement program. The results of the study show that there are several areas that are not recommended fordredging because they do not reach a minimum slope safety factor of 1.5.